An Investigation On The Use Of Ionic Liquid Loaded Magnetic Nanoparticle Grafted Β-Cyclodextrin Polymer For The Extraction Of Parabens - Yusoff, Masrudin Md (2017)
This work demonstrated on the use of magnetic nanoparticle (MNP) grafted onto the polymer as an adsorbent for the removal and extraction of endocrine disruptor chemicals (EDCs), namely paraben compounds, i.e. methyl paraben (MP), ethyl paraben (EP), propyl paraben (PP), butyl paraben (BP) and benzyl paraben (ArP). In this study, a simple and efficient superparamagnetic coated polymeric adsorbent was successfully synthesized via a co-precipitation method. Firstly, β-cyclodextrin (βCD) was polymerized using toluene-2,4- diisocyanate (TDI) linker before it was grafted onto MNP to form MNP-βCD-TDI.